PENGEMBANGAN APLIKASI TEBAK ANGKA BERBASIS ANDROID SEBAGAI MEDIA PERMAINAN EDUKATIF - Jumrah Dewi Yanti; Syaban Syaban; Iskandar Iskandar; Nur Fitrianingsih (Universitas Aisyiyah Surakarta, 2026)
The rapid development of mobile technology, especially Android, provides opportunities in the development of learning media and educational games. This study aims to develop the Android-based Tebak Angka application that can be used as entertainment while training users’ logical thinking skills. The method used includes design, implementation, and testing stages using Android Studio with Java programming language. The developed application features a main menu, difficulty level selection, game timer, hint system, playing chances, high score storage, and sound effects. Testing results show that the application runs well on Android devices and provides an engaging experience for users. This application has potential to be used as an educational game medium for elementary school students.